Modelling the Impact of Intellectual Capital on Firm Sustainability: A Case of Indonesian Consumer Goods Companies - Mudjijah, Slamet (Journal of Ecohumanism, 2024)
This research aims to analyze intellectual capital components such as human capital, structural capital, employed capital, and sustainable growth, as well as their relationship with financial performance.The study concentrates on Consumer Goods Industry firms listed on the Indonesia Stock Exchange. The research involved 27 companies chosen via purposive sampling for the study. The IBM SPSS software is used as the analytical instrument for performing numerous linear regression analyses.This research has shown that the development of sustainable growth is influenced by human capital, structural capital, and relationship capital. The financial performance factor can boost the influence of intellectual capital on sustainable development. The research reveals a new link between intellectual capital and sustainable development by examining financial performance as a moderating element.The study utilized financial reports from companies in Indonesia's consumer goods industry for data collection. The characteristics of each company sector vary, so the research findings cannot be extrapolated to companies in different sectors, like the service sector.